A very high infection intensity of Schistosoma mansoni in a Ugandan Lake Victoria Fishing Community is required for association with highly prevalent organ related morbidity. - Edridah M Tukahebwa; Pascal Magnussen; Henry Madsen; Narcis B Kabatereine; Fred Nuwaha; Shona Wilson; Birgitte J Vennervald (Public Library of Science (PLoS), 2013)
Background In schistosomiasis control programmes using mass chemotherapy, epidemiological and morbidity aspects of the disease need to be studied so as to monitor the impact of treatment, and make recommendations accordingly. These aspects were examined in the community of Musoli village along Lake Victoria in Mayuge district, highly endemic for Schistosoma mansoni infection. Methodology and principal findings A cross sectional descriptive study was undertaken in a randomly selected sample of 217 females and 229 males, with a mean age of 26 years (SD ± 16, range 7-76 years). The prevalence of S. mansoni was 88.6% (95% CI: 85.6-91.5). The geometric mean intensity (GMI) of S. mansoni was 236.2 (95% CI: 198.5-460.9) eggs per gram (epg) faeces. Males had significantly higher GMI (370.2 epg) than females (132.6 epg) and age was also significantly associated with intensity of infection. Levels of water contact activities significantly influenced intensity of infection and the highest intensity of infection was found among people involved in fishing. However, organomegaly was not significantly associated with S. mansoni except for very heavy infection (>2000 epg). Liver image patterns C and D indicative of fibrosis were found in only 2.2% and 0.2%, respectively. S. mansoni intensity of infection was associated with portal vein dilation and abnormal spleen length. Anaemia was observed in 36.4% of the participants but it was not associated with S. mansoni infection intensity. Considering growth in children as one of the morbidity indicators of schistosomiasis, intensity of S. mansoni was significantly associated with stunting. Conclusion Although organ-related morbidity, with the exception of periportal fibrosis, and S. mansoni infections were highly prevalent, the two were only associated for individuals with very high infection intensities. These results contrast starkly with reports from Ugandan Lake Albert fishing communities in which periportal fibrosis is more prevalent.